An Analysis of Idiom Types in English Film Dialogue and Their Translation Strategies in Indonesian Subtitles of the Kingsman Trilogy - Utami, Putri; Adrefiza, Adrefiza; Handayani, Reli (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
Idiomatic expressions are an important element in film dialogue because they convey figurative meaning, cultural values, and pragmatic functions. However, translating idioms into Indonesian subtitles often presents problems due to cultural differences and audiovisual technical constraints such as limited space and time. This study aims to analyze the types of idiomatic expressions found in the English film dialogue of the Kingsman trilogy and the translation strategies used in the Indonesian subtitles. This research employs a qualitative descriptive method with content analysis. The data consist of idioms identified from the English dialogue and their translations in Indonesian subtitles. Idiom types are classified based on McCarthy and O’Dell’s typology, while translation strategies are analyzed using Baker’s framework. The findings show that semi-idioms are the most dominant type and that paraphrasing is the most frequently used translation strategy. Abstrak Ekspresi idiomatik merupakan unsur penting dalam dialog film karena menyampaikan makna figuratif, nilai budaya, dan fungsi pragmatik. Namun, penerjemahan idiom dalam subtitle bahasa Indonesia sering menghadapi permasalahan akibat perbedaan budaya serta keterbatasan teknis audiovisual seperti ruang dan waktu. Penelitian ini bertujuan untuk menganalisis jenis-jenis idiom yang terdapat dalam dialog film berbahasa Inggris pada Kingsman trilogy dan strategi penerjemahan yang digunakan dalam subtitle bahasa Indonesia. Penelitian ini menggunakan metode deskriptif kualitatif dengan analisis isi. Data berupa idiom yang diidentifikasi dari dialog film berbahasa Inggris dan terjemahannya dalam subtitle bahasa Indonesia. Klasifikasi idiom didasarkan pada tipologi McCarthy dan O’Dell, sedangkan strategi penerjemahan dianalisis menggunakan kerangka Baker. Hasil penelitian menunjukkan bahwa semi-idiom paling dominan dan parafrasa menjadi strategi yang paling sering digunakan.